Social media at work : how networking tools propel organizational performance - Jue, Arthur L., 1966-; Marr, Jackie Alcalde, 1962-; Kassotakis, Mary Ellen, 1953- (San Francisco, CA : Jossey-Bass, 2010)
"The definitive guide for using social media to build more effective organizations. Today's networking technologies-wikis, blogs, and socia l networking sites-are changing how we build professional relationships and work collaboratively. In this insightful book, three organizationa l development experts from Oracle Corporation offer executives down-to- earth strategies for leveraging the power of social media to build more effective and agile organizations, engage employees, and sustain compe titiveness. Offers practical advice for using social media (wikis, blog s, and social networking sites) to increase organizational effectivenes s. Presents proven recommendations for building teams, accelerating lea rning, and fostering innovation by adopting social networking tools. Sh ows how to tap into the power of social networks to improve organizatio nal performance. Demonstrates how social media will help organizations thrive for years to come by drawing on case studies from companies like Intel, Cisco, Nokia, and others"--Provided by publisher.
Social media at work -- The changing landscape and what it means to you -- What is social media, and how does it work? -- Where social medi a has an impact -- Examples from trailblazers -- Putting social media t o work -- Looking to the future -- Notes -- Acknowledgments -- About th e authors -- Index.
Includes bibliographical references and index.
Keywords: Social media; Social networks; Organization